Risk of Stroke and Myocardial Infarction After Sudden Sensorineural Hearing Loss: A Meta‐Analysis. (6th November 2020) - Lammers, Marc J. W.; Young, Emily; Westerberg, Brian D.; Lea, Jane
Abstract : Objectives/Hypothesis: The pathophysiology of idiopathic sudden sensorineural hearing loss (ISSNHL) is still unknown, but labyrinthine artery infarction has been proposed. The objective of this study was to perform a systematic review and conduct a meta‐analysis assessing the risk of developing stroke and myocardial infarction after presentation with ISSNHL. Methods: A systematic literature review was conducted using Pubmed, Embase, Web of Science, and Cochrane Libraries. All studies investigating an association between ISSNHL and stroke and/or myocardial infarction (MI) were included. Adhering to the MOOSE guideline, two independent reviewers extracted data, assessed risk of bias, and evaluated the relevance and quality of evidence. Results: Three observational studies evaluating the risk of stroke in ISSNHL were included (n = 6, 521 patients). All individual study results indicated an increased relative risk of stroke after ISSNHL (unadjusted relative risk range 1.21–1.63). Pooled adjusted hazard ratios revealed a 1.42‐fold increased risk of stroke after ISSNHL (hazard ratio [HR] 1.42; 95% confidence interval [CI] 1.15–1.75, I 2 = 55%). Subgroup analysis of one study demonstrated that the increased risk is only present in adults aged above 50 years (HR 1.23; 95% CI 1.07–1.42). Five observational studies evaluating the risk of MI in patients with ISSNHL were included (n = 61, 499 patients). Pooled analyses demonstrated that ISSNHL was not associated with MI (HR 1.08, 95% CI 0.87–1.34). Conclusion: ISSNHL may be an independent risk factor for the subsequent development of stroke especially in a subgroup of elderly patients. More studies are needed to confirm this association and to assess whether such patients would benefit from cardiovascular risk assessment and management to prevent future strokes. Laryngoscope, 131:1369–1377, 2021